Photovoltaic Cell Having Multiple Electron Donors - (:unkn) unknown (Konarka Technologies, Inc., 2010)
Photovoltaic cells having multiple electron donors and/or multiple acceptors, as well as related components, modules, systems, and methods, are disclosed.
Keywords: Photovoltaic cells; Organic Active Material Containing (136/263); Electron donors; H01L 31/00 (20060101); Multiple acceptors